The Importance of Different Visual, Observational and Instructional Media in Pedagogy - Akramova Nigora (Peerian Journals Publishing, 2022)
Although educational organization is implicitly concerned with the grouping of students for educational experiences and instruction, it does draw on psychological theories of learning to some level. That will require creating intricate schedules, but it will also provide the benefits of other, more strictly systems without adding a lot of their drawbacks. For one thing, maintaining some age-based grouping is crucial as a link to extracurricular activities, where age peers frequently spontaneously gather. We can explore some specific information about the value of various visual, observational, and instructional media in pedagogy in this article.
Keywords: visual; observational; instructional; media